(untitled) (Research, Society and Development, 2022)
The aim of this study was to perform a systematic review to assess the effects of ozone therapy in dentistry. The databases used were Pubmed, Embase, Web of Science, and OpenGrey. The keyword: “Ozone” combined with one of the following keywords: “Dentistry”, “Teeth”, “Tooth”, “Enamel” and “Mouth” were used to search, only randomized clinical trials were included. The ROB2.0 tool was used to assess the risk of bias. 36 articles were included, 7 were classified as a low risk of bias, 17 as an uncertain risk and 12 as a high risk. For the most part, the articles dispelled results in the most diverse areas of dentistry and ozone has broadly broad applicability, however the large number of articles classified as having a high risk of bias or uncertain risk may be a limiting factor in the evidence found. Ozone therapy shows satisfactory results in its application in dentistry, however, due to the large number of articles with high or uncertain risk of bias, our evidence is limited. More randomized clinical trials are needed to assess the real benefits of ozone therapy in dentistry.